P-153 A hospice-wide project to develop and support multi-professional participation in clinical audit. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Levy, Jean; Chester, Rosie; Doyle, Chris; Glen, Gordon; Ross, Joy
Abstract : Background: Clinical audit within the organisation was perceived as piecemeal and lacking focus: staff lacked motivation and/or confidence to carry out audits. A new programme was devised to inspire and enthuse staff to examine areas of interest, encourage ownership of improvement activities, build staff skills in audit, and to boost multi-professional team working. A project was established, involving clinical, managerial and other staff, focusing on a particular area (discharge). Aim: The project aimed to achieve: Greater staff involvement in clinical audit; A training programme to improve staff knowledge of and interest in clinical audit, and address the organisation's audit priorities; Identification of other priorities for quality improvement projects; Support for completion of specific audits. Method : A project lead oversaw and drove the project by: Developing and delivering training courses and materials; Establishing quality improvement projects; Supporting staff to complete those projects over a three month period. Staff were invited to participate by their managers. A series of six workshops covered the stages of audit. The overarching topic was discussed and broken down into different areas for examination by groups. The groups were supported with their individual projects. Results: Six projects included communication, information sharing and timings. Participants agreed items of most concern/interest, learned where to find evidence and standards; how to design tools, collect, analyse and present data. Participants enthusiastically presented results and identified areas for improvement together. Groups were multidisciplinary and demonstrated benefit from examining processes objectively. Discussion/conclusions: Support through tailored workshops and individual advice meant each group completed their project and participants were enthusiastic in championing changes to improve care. Confidence increased and multi-professional groups worked well together. Further refinement could improve the programme which is to be repeated with a different focus. Lessons learnt included ensuring good communication about the programme and getting the timings of workshops right.